IMPLEMENTASI PEMBUATAN SUMUR RESAPAN BERDASARKAN PERATURAN DAERAH KOTA PEKANBARU NOMOR 10 TAHUN 2006 TENTANG SUMBER DAYA AIR DAN SUMUR RESAPAN DI KELURAHAN TANGKERANG LABUAI KOTA PEKANBARU - Rahmat Sentosa Daeli; Mexsasai Indra; Rika Lestari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Pekanbaru City Regional Regulation Number 10 of 2006 concerning Water Resourcesand Infiltration Wells Article 19 paragraph (1) stipulates "Every applicant for a Building Permitis required to plan and construct infiltration wells. Making infiltration wells is the developer'sobligation in housing areas in Tangkerang Labuai Village, but based on facts on the ground, 20housing estates in Tangkerang Labuai Village do not build infiltration wells. The purpose of thisresearch is to find out; first, Implementation of Infiltration Well Development Based onPekanbaru City Regional Regulation Number 10 of 2006 concerning Water Resources andInfiltration Wells in Tangkerang Labuai Village, Pekanbaru City, second, inhibiting factors forImplementation of Infiltration Well Development Based on Pekanbaru City Regional RegulationNumber 10 of 2006 concerning Water Resources and Infiltration Wells in Tangkerang LabuaiVillage, Pekanbaru City, thirdly, efforts to maximize the implementation of making infiltrationwells based on Pekanbaru City Regulation Number 10 of 2006 concerning Water Resources andInfiltration Wells in Tangkerang Labuai Village, Pekanbaru City.The type of legal research used by the author is sociological legal research. In thissociological study the authors took primary data and secondary data with the population andsamples, namely the Office of Investment and One Stop Integrated Services (DPMPTSP)Pekanbaru City, Public Works and Spatial Planning (PUPR) Pekanbaru City, HousingDevelopers in Tangkerang Labuai Village, Practitioners Pekanbaru City Planning, Secretary ofthe Lurah of Tangkerang Labuai Village, Head of RW in Tangkerang Labuai Village andresidents of housing in Tangkerang Labuai Village.Based on the results of this study, it can be concluded that the Implementation of MakingInfiltration Wells Based on Pekanbaru City Regulation Number 10 of 2006 concerning WaterResources and Infiltration Wells in Tangkerang Labuai Village, Pekanbaru City does not work atall. This is because the relevant Regional Apparatus Organizations (OPD) have not implementedthe Perda a quo properly and law enforcement against permit applicants who do not buildinfiltration wells is not carried out and the monitoring process is not carried out properly.Keywords: Implementation-Infiltration Wells-Regional Regulations-Building Permit (IMB)